PERKEMBANGAN SISTEM MANAJEMEN K3 DALAM INDUSTRI KONSTRUKSI: SEBUAH SYSTEMATIC LITERATURE REVIEW - Khairiyah Dwie Vanesa; Asila Tiara Putri; Hafizza Salsabilla Tarigan; Sri Hajijah Purba (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
The construction industry is one of the sectors with the highest risk of workplace accidents. This study aims to review the development of Occupational Health and Safety Management Systems (OHSMS) in the Indonesian construction industry through a systematic literature review. The method used is a qualitative descriptive literature study of five national and international journals related to OHSMS in construction. The results show an increase in awareness and commitment to OHSMS, especially among large construction companies. However, there is still a gap between commitment and practical implementation. Key challenges include lack of communication, improper use of PPE, lack of training, and particularly the absence of a safety culture. The study concludes that despite progress, significant efforts are still needed to translate policies into practice, build a strong safety culture, and ensure all parties, especially contractors, take full responsibility for safety.